Routes and roots to knowing in Shaun White`s snowboarding road trip: A mycorrhizaic approach to multisensory emplaced learning in exergames - Bäckström, Å.; Quennerstedt, M.; Maivorsdotter, N.; Meckbach, J. (Scandinavian Sport Studies Forum, 2019)
This article explores learning during game-play of a snowboarding video game intrigued by questions raised in the wake of the increasing mediatisation and digitisation of learning. Correspondingly, we answer to calls for more suitable metaphors for learning to cater for the entangled learning processes that changes related to the increase of digital media may infer. Using a short term sensory ethnography approach, we elaborate on the idea of multisensory emplaced learning and propose an organic metaphor - mycorrhiza - to both methodology and learning. Mycorrhiza refers to a symbiotic relationship between fungi and roots of plants in its environment where fungi are the visible effects of the mycorrhiza. The metaphor provides a way to start to unpack sensory, visual and embodied aspects of learning in the complexities of the digital age. By elaborating on the mycorrhizaic concepts fungus, soil, growth, mycelia and symbiosis we show three interrelated ways of moving through this game: (i) a social and cultural route, (ii) a competitive route, and (iii) an experiential route. With help of the metaphor we discern the symbiotic relations between what appeared in our empirical material as visual and other human and non-human aspects of emplacement.